Frontiers in Lichen Planopilaris and Frontal Fibrosing Alopecia Research: Pathobiology Progress and Translational Horizons - Maryanne Makredes Senna; Erik Peterson; Ivan Jozic; Jérémy Chéret; Ralf Paus (Elsevier, 2022)
Lichen planopilaris (LPP) and frontal fibrosing alopecia (FFA) are primary, lymphocytic cicatricial hair loss disorders. These model epithelial stem cell (SC) diseases are thought to result from a CD8+ T-cell‒dominated immune attack on the hair follicle (HF) SC niche (bulge) after the latter has lost its immune privilege (IP) for as yet unknown reasons. This induces both apoptosis and pathological epithelial‒mesenchymal transition in epithelial SCs, thus depletes the bulge, causes fibrosis, and ultimately abrogates the HFs' capacity to regenerate. In this paper, we synthesize recent progress in LPP and FFA pathobiology research, integrate our limited current understanding of the roles that genetic, hormonal, environmental, and other factors may play, and define major open questions. We propose that LPP and FFA share a common initial pathobiology, which then bifurcates into two distinct clinical phenotypes, with macrophages possibly playing a key role in phenotype determination. As particularly promising translational research avenues toward direly needed progress in the management of these disfiguring, deeply distressful cicatricial alopecia variants, we advocate to focus on the development of bulge IP and epithelial SC protectants such as, for example, topically effective, HF‒penetrating and immunoinhibitory preparations that contain tacrolimus, peroxisome proliferator-activated receptor-γ, and/or CB1 agonists.